(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Congenital hearing loss is one of the most common sensory disorders in children and has profound effects on speech, language, cognitive development, and social integration if not detected and treated early. Objective: This review aims to summarize current evidence on the prevalence, causes, clinical characteristics, age at detection, and timing of intervention in children with congenital hearing loss. Methods: A narrative review of national and international literature was conducted using major scientific databases and official reports from 1998 to 2025. Relevant studies addressing epidemiology, etiology, clinical features, early detection, and intervention outcomes of congenital hearing loss were analyzed and synthesized. Results: The prevalence of congenital hearing loss is estimated at approximately 1–3 per 1,000 live births worldwide. Genetic factors account for more than half of cases, while prenatal and perinatal causes such as congenital infections, prematurity, severe neonatal jaundice, and ototoxic exposure remain significant contributors. Sensorineural hearing loss is the most common type, often presenting without obvious symptoms at birth, leading to delayed diagnosis in the absence of newborn hearing screening. Early detection and intervention, particularly within the first 6 months of life, are consistently associated with better auditory and language outcomes. Conclusion: Congenital hearing loss represents a major public health concern. Universal newborn hearing screening, early diagnosis, and timely intervention are critical to optimizing developmental outcomes and improving quality of life for affected children.